EIGHTEEN WHEELS of STEEL DALAM FOTOGRAFI SENI - Aran Handoko (SURYA SENI, 2008)
“Eighteen of Wheels of Steel in Art Photography.” This project is aimed at expressing the photographer’s feelings and deepest aesthetic emotions based on his experiences with the existence of the heavy duty vehicles. The basis of photography is an expression media through the aesthetic and artistic instinct according to the elements of art and composition such as color, line, balance, light and dark, rhythm, and angle.The concept of this creation of photographic works is Eighteen (18) Wheels of Steel in art photography. The objects here are focused on heavy duty vehicles i.e. 18 Wheels of Steel, which are also or called trailers. The objects taken as the photography resources are presented in the representations of realistic forms as well as abstract patterns which can embody the artistic language of emotive expression using a creative and aesthetic approach. These works of photography therefore take the forms of expression based on the photographer’s experiences with the existence of the heavy duty vehicles which are cruisers or huge, strong, powerful vehicles. The creation of these photographicworks was based on the expression as a basic pattern of creation relying on the colors and forms of the objects with aesthetic considerations based on the creative ideas and technical competences. So that the results from thisphotographic creation are not just forms of documentations but forms of art work presentations on a creative-aesthetic level as well.The approach is focused on the creative-aesthetic aspect which emphasized composition manipulations and photographic techniques such as the selection of objects, using the exact exposures, using the picture formats, and the angle ofshooting. These techniques of course were used based on photographic technical considerations which were oriented to possibilities in practical implemen- tations. In this respect, therefore, in order to ﬁ t the works to the concepts, a thematic grouping of trailers was done, based on detail, reﬂ ection, on moving, and silhouette. The works of photography, therefore, will offer new experiences in  perceiving trailers. In photographic view, trailers basically have distinct aestheticvalues as objects of photography which will enrich the spectators’ visual insight. Keywords : 18 Wheels of Steel, Fine Art Photography, and Creative-aesthetic